Disorders of Temporality and The Subjective Experience of Time: Unresponsive Objects and the Vacuity of the Future. Issue 2 (3rd March 2016) - Seligman, Stephen
Abstract : This paper explores how the personal sense of time—temporality—is organized and experienced in different clinical situations. It uses examples from infancy observations to draw links between caregivers' response to infants' capacities for motor activity and emotional communication and the development of the senses of personal security, vital intersubjectivity and temporality, that is, the feeling of a meaningful self and an open future. In illustrations from both early child–parent interaction and an extended case, it suggests how moment-to-moment interactions reflect and sustain these core, highly personal experiences of what it feels like to live in the world, that is, how an accretion of "micro" interactions can contribute to and help us understand the "macro" structures that analysts usually describe, such as intersubjectivity, the sense of self, and here, the senses of time. With that in mind, the paper evokes a few specific "disorders of temporality." One group of these involves the blurring of past and present, especially following trauma. Much of the paper, though, is concerned with a basic deficit in the sense of time that can be observed, when the patient presents without the hope that new experiences can emerge, however fitfully, with the feeling of a forward-moving future. In an imaginative move, the paper links this image with the experience of an infant with an unresponsive parent, one who does not afford that infant the most basic senses of personal agency that come from having her feelings and gestures recognized and responded to in a way that gives her the feeling that she is having some effect on her world. Clinical implications are drawn, often demonstrating how brief moments of analytic interaction reflect the macrocosms of the broader analytic relationship and the patient's psychological organization.